Socio-demographic variables as determinants of Violence in Sports among Secondary School Students in Nsukka Education Zone, Enugu State, Nigeria - Odo, Chinwe Stella; Joel, Kerimu Ikazuwagbe; Asogwa, Louisa Nkemdilim; Ngwoke, Saint Oliver Rotachukwu; Aina, Micheal Gbemisola; Umeakuka, Okey Aaron (International Journal of Human Kinetics, Health and Education, 2025)
Violence in sports has become a global challenge and it has greatly affected sports participation among young people. The objective of this study was to investigate age and gender as determinants of violence in sports among secondary school students in Nsukka Education Zone, Enugu State, Nigeria. A descriptive survey study was conducted on 383 students. A multi-stage sampling technique was used to select the study sample. The instruments for data collection were a researcher-developed questionnaire titled "Determinants of Violence in Secondary Schools Sports Questionnaire" (DVSSSQ). The face validity of the instruments was established and the internal consistency of DVSSSQ was determined using Split half (Spearman-Brown Coefficient Correlation) with indices of .724. Frequency measures and binary logistic regression were used to analyse the data. Results showed that age is a significant determinant of violence in secondary school sports in Nsukka Education Zone (p=0.001). While, gender is a not significant determinant of violence in secondary school sports in Nsukka Education Zone (p=0.263). The study concluded among others that secondary school students aged 15 years and above were 2.39 times more likely to experience violence in secondary school sports than those less than 15 years. Consequently, school sports administrators should create awareness among students on the need for and importance of avoiding violence during sporting activities and endeavour to punish offenders appropriately.